Organo-Complexing Leaching of Iron from Indegeneous Bauxite - Ikram Aujla, Muhammad; Akram Kashmiri, Muhammad; Hussain, Muhammad; Ismail, Tariq; Riaz, Tauheeda (Asian Journal of Chemistry, 2011)
Extraction of iron from bauxite ore was employed by phase extraction. Steps involved the formation and dispersion of the iron complex in aqueous phase and then extracting the iron complex by addition of organic solvent. Iron was complexed with oxalic acid and citric acid and the complex was extracted by adding ethyl acetate, chloroform and benzene as organic solvents. Chloroform gives 33 % of iron and 8.5 % extraction of aluminium with oxalic acid and 37 % extraction of iron and 10.2 % extraction of aluminium with citric acid (complexing agent). Benzene provides 30 % extraction of iron and 10 % extraction of aluminium with oxalic acid and 35 % extraction of iron along with 10.3 % that of aluminium with citric acid. Ethyl acetate gives different results of extraction by the phase separation method. Using oxalic acid, only 3.4 % extraction of iron and 9.29 % extraction of aluminium results, while 4.34 % iron extraction with citric acid were observed under the same conditions. The extraction of aluminium was zero, which is the requirement of the process. Comparison of extraction shows that chloroform and benzene give almost similar extraction results for aluminium and iron with citric acid and oxalic acid. Ethyl acetate give comparatively lesser extraction with both acid complexes but it gives direction towards removal of iron without removing useful aluminium from the ore sample.